Rút gọn biểu thức \(P=\dfrac{a^{\sqrt{3}+1}\cdot a^{2-\sqrt{3}}}{\left(a^{\sqrt{2}-2}\right)^{\sqrt{2}+2}}\) với \(a>0\).
\(P=a\) | |
\(P=a^3\) | |
\(P=a^4\) | |
\(P=a^5\) |
Chọn phương án D.
Dùng máy tính cầm tay: r \(a=2\) ta được $$P=2^n=32=2^5$$Vậy \(P=a^5\).
Chọn phương án D.
\(\begin{aligned}
P&=\dfrac{a^{\sqrt{3}+1}\cdot a^{2-\sqrt{3}}}{\left(a^{\sqrt{2}-2}\right)^{\sqrt{2}+2}}=\dfrac{a^{\sqrt{3}+1+2-\sqrt{3}}}{a^{\left(\sqrt{2}-2\right)\left(\sqrt{2}+2\right)}}\\
&=\dfrac{a^3}{a^{-2}}=a^{3-(-2)}=a^5.
\end{aligned}\)